Radical Interrelated Qualitative Space in the Midst of Multipandemics: A Collaborative Scholarly Personal Narrative. (December 2021) - Combs, Lisa Delacruz; Dellarosa, Maretha; Kim, Myung-Jin; Pittman, Alexander G-J; Gilbert, Chelsea; Smith, Spencer J.; Smith, Tessa; Valley, Shay N.; Pasque, Penny A.
Given the current unprecedented multiple pandemics of COVID-19, anti-Black and anti-Asian violence, and white supremacy, we—a group of graduate students and a faculty member who hold diverse identities across disciplines, race, gender, nationality, and additional categories—came together to focus on qualitative research as an ontological, epistemological, and axiological space toward community and culture change. Specifically, we took up scholarly personal narrative, which centers postmodernism and focuses on the reality that "we see what we believe; we observe what we narrate; we transform what we reframe." What emerged were radical interrelated understandings of privilege, guilt, and the importance of kinship. As such, this vulnerable group reflected on graduate student experiences with multiple pandemics and how the academy may enact transformative change, reframing our own understandings of qualitative space.